ROLE OF BIOGENIC AMINES ON MIGRATION OF DISTAL RETINAL PIGMENTS OF THE FRESHWATER PRAWN, MACROBRACHIUM KISTNENSIS - MACHALE, P. R.; SAROUNI, R.; NAGABHUSHANAM, R. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1988)
Effect of serotonin, dopamine, norepinephrine and acetylcholine on distal retinal pigment migration of M. Kistinensis has been determined. Serotonin and dopamine induced dark adaptation. Moretter, norepinephrine and acetylcholine produced light adaptation. Response observed was dose dependent.